Influence of ownership structure on earnings smoothing in companies listed on B3 - Teixeira, Clademir; Mazzioni, Sady; Magro, Cristian Baú Dal; Soschinski, Caroline Keidann; Valmorbida, Fernanda Prigol (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The aim of the study is to analyze the influence of ownership structure on earnings smoothing practices in companies listed on B3. The analysis considered multivariate linear regression for a sample of 203 observations, with data referring to the period 2016-2021. The results indicated that the greater presence of international and institutional investors are factors that mitigate earnings smoothing practices. In turn, ownership concentration, government ownership and growth in the number of shareholders in the stock market did not prove to be determinants of income smoothing. The results suggest that the low participation of institutional and international investors may make it necessary to use additional corporate governance mechanisms.